Effect of consumption of chia (Salvia hispanica) on constipation symptoms presented by students from a private university in Lima Este, 2014 - Bernal Altamirano, Eidi (2019)
Objetive: This research pretends to determine the effect of consumption of chia seed (Hispanic sage) about thesymptoms of constipation which presents the students of a private university of east Lima, 2014. Methods:The study is pre-experimental design and longitudinal cut. Results: The Treatment was applied in the group ofstudents with constipation for 3 weeks, which were divided into two subgroups consuming gelatin chia seeds25gr the Subgroup A and 15 gr the subgroup B. Conclusions: It was concluded that there is a significant decreasein symptoms of the constipation symptoms in the third week of treatment in both groups, being corroborated withthe McNemar test (p <0.05).